Type II secretion in Yersinia—a secretion system for pathogenicity and environmental fitness - von Tils, Dominik; Blädel, Inga; Schmidt, M A.; Heusipp, Gerhard (Frontiers in Cellular and Infection Microbiology, 2012)
In Yersinia species, type III secretion (T3S) is the most prominent and best studied secretion system and a hallmark for the infection process of pathogenic Yersinia species. Type II secretion (T2S), on the other hand, is less well-characterized, although all Yersinia species, pathogenic as well as non-pathogenic, possess one or even two T2S systems. The only Yersinia strain in which T2S has so far been studied is the human pathogenic strain Y. enterocolitica 1b. Mouse infection experiments showed that at least one of the two T2S systems of Y. enterocolitica 1b, termed Yts1, is involved in dissemination and colonization of deeper tissues like liver and spleen. Interestingly, in vitro studies revealed a complex regulation of the Yts1 system, which is mainly active at low temperatures and high Mg2+-levels. Furthermore, the functional characterization of the proteins secreted in vitro indicates a role of the Yts1 machinery in survival of the bacteria in an environmental habitat. In silico analyses identified Yts1 homologous systems in bacteria that are known as plant symbionts or plant pathogens. Thus, the recent studies point to a dual function of the Yts1 T2S systems, playing a role in virulence of humans and animals, as well as in the survival of the bacteria outside of the mammalian host. In contrast, the role of the second T2S system, Yts2, remains ill defined. Whereas the T3S system and its virulence-mediating role has been intensively studied, it might now be time to also focus on the T2S system and its role in the Yersinia lifestyle, especially considering that most of the Yersinia isolates are not found in infected humans but have been gathered from various environmental samples.